Educational Management Model of Sangha in Pathumthani Province Following of Policy One Sub-District One Mahãpariyatti (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research article were1) to study of educational management model of Sanghã in Pathumthani Province following of policy one Sub-District one Mahãpariyatti,2) to study the development of Model Sanghã’s Pãli ecclesiastical management from a educational Management model of Sanghã in Pathumthani Province following of Policy One Sub-District One Mahãpariyatti, and 3) to check of educational Management model of Sanghã in Pathumthani Province following of policy one Sub-District one Mahã. The methodology identified mixed method between the quantitative and quantitative research methods. The qualitative research collected data from 15 key informants, purposefully selected collecting data by face-to-face in-depthinterviewing with the structured in-depth-interview. Data were analyzed bydescriptive interpretation. Data were also collected by focus group discussion with 9participants. Data were also analyzed by descriptive interpretation. The quantitativeresearch collected data with questionnaires from 150 samples, analyzing data with descriptive statistics as frequency, percentile, meanand standard deviation, SD. The research results found that: 1) The conditions of educational management model of Sanghã in Pathumthani Province following of policy one Sub-District one Mahãpariyatti. Divided into seven sins, manage, course, faculty, learning and teaching, Grading Assessment, learning resources at the high level in all aspects. 2) Thedevelopment of educational Management model of Sanghã in Pathumthani Province following of Policy One Sub-District One Mahãpariyatti. Development of structure learning and teaching as well. Set the indicator to be effective. Teachers pedagogical content knowledge. Together with used to teach by technology. To create an incentive to want to learn more. 3) The teaching should be adjusted to the current language, content, image, and having educational media at all level.Teachers must have a good knowledge is there a way to teach students and to understandhow to apply with modern pedagogical knowledge.